THE EFFECT OF TEACHER PROFESSIONAL PERCEPTION, MOTIVATION AND SELF EFFICACY ON INTEREST TO BE TEACHER - Nurhasanah, Dwi; Suwandari, Lusi; Kurniasih, Retno (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research is a study that aims to determine the effect of the perception of the teaching profession, motivation, and self-efficacy on the interest in becoming a teacher for the students of the Economic Education Study Program at Jenderal Soedirman University. The population in this study were students of economic education from the 2017 to 2020 class who were active. The sampling technique in this study used a simple random sampling technique so that a sample of 129 students was obtained. Collecting data using a questionnaire or questionnaire method. The data analysis technique used is multiple regression analysis. Based on the results of research and data analysis using quantitative descriptive statistical analysis shows that the value of ttable = 1.98 so that the results obtained are: (1) There is a positive and significant influence on the perception of the teaching profession on interest in becoming a teacher, this is indicated by the tcount value of 3.649 and the level of significance of 0.000, (2) There is a positive and significant effect of motivation on interest in becoming a teacher, this is indicated by a t-value of 2.267 and a significance level of 0.025, (3) There is a positive and significant effect of self-efficacy on interest in becoming a teacher, this is indicated by the value of tcount is 5.298 and the significance level is 0.000.